Systematic Sex-Based Inequity in the MELD Score-Based Allocation System for Liver Transplantation in Germany - Leke Wiering; Leke Wiering; Annette Aigner; Marieke van Rosmalen; Brigitta Globke; Brigitta Globke; Tomasz Dziodzio; Nathanael Raschzok; Nathanael Raschzok; Münevver Demir; Wenzel Schöning; Frank Tacke; et al. (Transplant International)
In liver allocation systems based on the Model for End-stage Liver Disease (MELD) score, sex inequities have been identified in countries with high organ donation rates. Whether similar inequities exist in regions with average to low donation rates remained unclear. We assessed the impact of sex on transplantation rates, waiting list mortality and post-transplant survival in 25,943 patients waitlisted for liver transplantation in Germany between 2003 and 2017 using competing risk analysis. Women are currently underrepresented on the waiting list (33.3%) and among transplant recipients (31.1%) compared to their proportion of severe liver disease cases (35.1%). The introduction of MELD-based allocation has worsened this disadvantage [HR before: 0.89 (0.81–0.98), after: 0.77 (0.74–0.81)]. Three key factors contribute to this disparity: Women have lower creatinine levels despite worse renal function, reducing their MELD score (median 1, 0–3). Second, exceptional MELD points are more frequently granted to men [HR 1.61 (1.54–1.69) compared to regular allocation]. Third, the small height of women has the highest impact on the probability of not being transplanted [adjusted HR 0.85 (0.81–0.9)]. Even in countries with lower organ donation rates, MELD-based allocation leads to sex inequity. Measures are needed to ensure sex-neutral liver allocation in MELD-based systems worldwide.